2018
DOI: 10.1016/j.jtumed.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing professional identity through a community based education program: medical students experience

Abstract: Objectives Community-based education (CBE) has an impact on the types of medical students produced at the end of medical training. However, its impact on professional identity development (PID) has not been clearly understood. This study thus explores the effect of the CBE program on PID. Methods A qualitative phenomenological study was conducted on a group of Universiti Sains Malaysia medical students who had finished the Community and Family Case Study (CFCS) program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…[17][18][19] Community-based education (CBE) is suggested as a model for facilitating IPE in collaborative skills in the workplace. [20][21][22] CBE is defined as learning activities that use the community extensively as a learning environment, in which not only students but also teachers, members of the community, and representatives of other sectors are actively engaged throughout the educational experience. 23 Community-based IPE (CBIPE) is the process by which a group of two or more students from different health-related occupations with different educational backgrounds learn together while utilising the community as a learning environment, with collaboration and interaction as part of their learning goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Community-based education (CBE) is suggested as a model for facilitating IPE in collaborative skills in the workplace. [20][21][22] CBE is defined as learning activities that use the community extensively as a learning environment, in which not only students but also teachers, members of the community, and representatives of other sectors are actively engaged throughout the educational experience. 23 Community-based IPE (CBIPE) is the process by which a group of two or more students from different health-related occupations with different educational backgrounds learn together while utilising the community as a learning environment, with collaboration and interaction as part of their learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of CBIPE in specific community contexts have often been limited to specific settings like senior housing 32 or child healthcare. 34 To enable students to acquire comprehensive skills ranging from diagnosing health problems in the community, to formulating and implementing the problemsolving activities, 20,22 designing a CBIPE program providing those learning opportunities needed to be designed.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen papers described medical students’ self-reported skills acquisition (Kirkpatrick reaction criteria). In nine of these papers, students reported an increase in their research skills or knowledge and in two of which students reported an increased awareness of their research identity / thinking as a scientist [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In nine (53%) of these papers, the students reported an increase in their research skills or knowledge. In two (12%) of these papers, the students reported an increased awareness of their research identity / thinking as a scientist (25,26). Quality measure of primary studies: Su cient description of active research option 26 papers were rated to have had a su cient description of the active research option.…”
Section: Main Intercalated Degree Describedmentioning
confidence: 99%